ALGORITHM OF MANAGEMENT OF PATIENTS WITH SUSPECTED BLUNT CARDIAC TRAUMA - S. R. Gilarevsky; D. A. Kosolapov; P. A. Ivanov; I. M. Kuzmina; P. Yu. Lopotovskiy; A. K. Shabanov; O. V. Baturina (Неотложная медицинская помощь)
Abstract. Contemporary algorithm of diagnostic examination of patients with suspected blunt cardiac trauma is presented. General aspects of monitoring and treatment of such patients are also discussed.